Effects of inulin supplementation on intestinal barrier function and immunity in specific pathogen-free chickens with Salmonella infection. (2nd January 2020) - Song, Jiao; Li, Qinghe; Everaert, Nadia; Liu, Ranran; Zheng, Maiqing; Zhao, Guiping; Wen, Jie
Abstract: We investigated the effects of inulin on intestinal barrier function and mucosal immunity in Salmonella enterica serovar Enteritidis (SE )–infected specific pathogen-free (SPF ) chickens. SPF chickens ( n = 240, 1-d-old) were divided into 4 groups (6 replicates per group, 10 chickens per replicate): a control group (CON ) fed a basal diet without inulin supplementation and 3 SE-infected groups fed a basal diet supplemented with inulin 0% (SE group ), 0.5% (0.5% InSE group ), and 1% (1% InSE group ), respectively. At 28 d of age, the chickens in SE-infected groups were orally infected with SE and in CON group were administrated with phosphated-buffered saline (PBS). Intestinal morphology, mucosal immunity, and intestinal barrier function-related gene expression were analyzed at 1- and 3-d post-infection (dpi ). SE challenge significantly increased the mucosal gene expression, such as interleukin-1β ( IL-1β ), lipopolysaccharide-induced tumor necrosis factor factor ( LITAF ), interferon-γ ( IFN-γ ), and interleukin-6 ( IL-6 ), and increased serum IFN-γ, secretory IgA (sIgA), and IgG concentration, and significantly decreased the gene expression levels of mucin 2 ( MUC2 ) and claudin-1 at 3 dpi compared with the CON group ( P < 0.05). Inulin supplementation improved the expression levels of these immunity- and intestinal barrier function-related genes, increased villus height (VH ), and decreased crypt depth (CD ) in the duodenum, jejunum, and ileum at 1 and 3 dpi within the SE-challenged groups ( P < 0.05). SE challenge significantly increased ileal Toll-like receptor 4 ( TLR4 ) mRNA at 1 and 3 dpi, suppressor of cytokine signaling 3 ( SOCS3 ) mRNA at 1 dpi, and phospho-signal transducer and activator of transcription 3 (p-STAT3 ) and Janus kinase1 (JAK1 ) protein expression at 3 dpi compared with the CON group ( P < 0.05). Inulin supplementation suppressed p-STAT3 and JAK1 protein expression and promoted ileal TLR4 and SOCS3 mRNA expression at 3 dpi compared with SE group ( P < 0.05). In conclusion, inulin alleviated SE-induced gut injury by decreasing the proinflammatory response and enhancing mucosal immunity in chickens.